(untitled) (Research, Society and Development, 2022)
Millions of years ago humans have been using plants for medicinal purposes. They are used to treat and cure various diseases, including mental disorders such as depression and anxiety. Anxiety has become one of today’s biggest problems. The study aimed to present the pharmacological action of lemon balm, mint, passion fruit and valerian in the intervention of anxiety in pharmaceutical offices. The materials used were articles published between 2015 and 2022 in the databases of the Virtual Health Library (VHL), latin american and caribbean literature on health sciences (LILACS), the Scientific Electronic Library Online (SciELO), capes journals, data from the Brazilian Ministry of Health (MS) and the National Agency for Sanitary Surveillance (ANVISA). Studies show the importance of the use of medicinal plants in the treatment of anxiety, a practice passed down from generation to generation and used by all social classes. The profile of the clinical consultation has grown and will continue to grow more and more as a result of successful visits by patients to the office, where pharmacists find the means to optimize the quality of life of the patient in relation to the analysis and screening of therapeutic prescriptions, in pharmaceutical care. For a bibliographic study, showing alternatives to drugs for anxiety as final alternatives and integrative approaches to health benefits, looking at these four plants investigates their clinical efficacy, chemical properties, benefits and botanical and pharmacological characteristics.